2009
DOI: 10.1055/s-0029-1186237
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of the Cinnamon Oil fromCinnamomum zeylanicumupon Early Stage Diabetic Nephropathy

Abstract: The current study was designed to evaluate the ameliorative effect of the cinnamon oil upon early stage diabetic nephropathy owing to its antioxidant and antidiabetic effect. Cinnamon oil was extracted by hydro-distillation of the dried inner bark of Cinnamomum zeylanicum Blume. Further characterization of the extracted oil was carried out using IR, (1)H-NMR, and (13)C-NMR techniques. Early stage of diabetic nephropathy was induced by administration of alloxan (150 mg/kg, I. P.). Cinnamon oil was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 27 publications
4
46
0
Order By: Relevance
“…Alloxan is well documented to induce persistent hyperglycemia by the generation of ROS (Duzguner & Kaya, 2007). These free radical species result in oxidative damage to the heart, kidneys, eyes, nerves, liver, small and large vessels and gastrointestinal system (Mishra et al, 2010). Inflammatory changes, hypertrophic remodeling and cell death have been reported to occur in the diabetic hearts in experimental animals as early as 7 days after the induction of the diabetic state (Cai et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Alloxan is well documented to induce persistent hyperglycemia by the generation of ROS (Duzguner & Kaya, 2007). These free radical species result in oxidative damage to the heart, kidneys, eyes, nerves, liver, small and large vessels and gastrointestinal system (Mishra et al, 2010). Inflammatory changes, hypertrophic remodeling and cell death have been reported to occur in the diabetic hearts in experimental animals as early as 7 days after the induction of the diabetic state (Cai et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] Cinnamon has also increased endogenous insulin production, and ameliorated the nephropathy occurring sometimes at the early stage of diabetes. [12][13][14] Most of the studies on cinnamon have therefore confirmed its diabetic effect to be insulinpotentiating, although the effects independent from insulin have not yet been elucidated. Altschuler et al have performed a prospective, double-blind, placebocontrolled study on cinnamon using adolescent type 1 diabetic subjects, and no significant effect on suppressing hemoglobin A1c was found.…”
mentioning
confidence: 99%
“…For example, cinnamaldehyde ( Fig. 1A) from C. zeylanicum has been shown to exert protective effects against alloxan-induced renal damage by reducing glomerular expansion, eradicating hyaline casts, and decreasing tubular dilatations (Mishra, Bhatti, Singh, & Singh Ishar, 2010). Another large group of polyphenolic compounds flavonoids also show anti-DN activity.…”
Section: Bioactive Components From Tcm Edible Plantsmentioning
confidence: 98%